Biotechnological transformation of giant miscanthus biomass into bacterial nanocellulose - Shavyrkina, N. A.; Gladysheva, E. K.; Zenkova, A. A.; Skiba, E. А. (Proceedings of Universities. Applied Chemistry and Biotechnology, 2025)
Biotechnological transformation of plant materials constitutes one of the most promising industrial processes for obtaining high-value products from inexpensive plant materials. The article analyzes the biotransformation of giant miscanthus (Miscanthus × giganteus) into high-value bacterial nanocellulose from the feedstock to the final product, i.e., presents the complete cycle of plant material processing. First, the chemical composition of giant miscanthus biomass was determined, and the content of cellulose was found to be 54%. After that, biotransformation was performed in three stages: in the first stage, the giant miscanthus biomass was pretreated using four methods; then, the obtained substrates were subjected to enzymatic hydrolysis under the same conditions, and carbohydrate growth media were obtained; in the final stage, bacterial nanocellulose was biosynthesized in the obtained growth media using Medusomyces gisevii Sa-12 symbiotic culture. The chemical pretreatment with dilute solutions of nitric acid and sodium hydroxide was found to be extremely effective and increase the reactivity to enzymatic hydrolysis by 28–31 times as compared to native miscanthus. It is shown that for the production of bacterial nanocellulose from giant miscanthus, biomass should undergo one-stage pretreatment with a dilute nitric acid solution. In this case, the substrate yield from the feedstock (for subsequent hydrolysis) amounts to 50%, the extraction of reducing sugars from miscanthus biomass is maximum (65.2%), and the yield of bacterial nanocellulose is 1.1–1.3 times higher than for the other three biomass pretreatment methods.